The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/mpg.0000000000003566
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy in Infants With Gastrointestinal Bleeding Has Limited Diagnostic or Therapeutic Benefit

Abstract: Objectives: Pediatric gastroenterologists are often consulted to perform diagnostic and therapeutic endoscopy in infants with gastrointestinal bleeding (GIB). The value of endoscopy and risk of complications in this population are not well characterized. We aimed to describe findings and outcomes of infants with GIB who undergo endoscopy. Methods: Retrospective, single-center, cohort study of hospitalized infants ≤12 months who underwent esophagogastroduodenoscopy (EGD) and/or colonoscopy/flexible sigmoidosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Age more than 4 years was a positive predictor to reach a diagnosis via endoscopy while the presence of melena alone without hematemesis was a negative predictor. Similarly, Bose and associates [25] found that endoscopy in infants with gastrointestinal bleeding had limited diagnostic benefit, while Yu and colleagues [19] stated that the diagnostic yield was higher among children suffering from hematemesis and melena than in those suffering from any of them separately.…”
Section: Predictors Of Positive Yield and Etiologymentioning
confidence: 99%
“…Age more than 4 years was a positive predictor to reach a diagnosis via endoscopy while the presence of melena alone without hematemesis was a negative predictor. Similarly, Bose and associates [25] found that endoscopy in infants with gastrointestinal bleeding had limited diagnostic benefit, while Yu and colleagues [19] stated that the diagnostic yield was higher among children suffering from hematemesis and melena than in those suffering from any of them separately.…”
Section: Predictors Of Positive Yield and Etiologymentioning
confidence: 99%
“…The value of endoscopy and risks for complications in infants with gastrointestinal bleeding (GIB) were described in a study of 56 infants with GIB from 2008 to 2019 (51.8% female; mean age 161.6 days) (23). Seven endoscopies identified sources of GIB: gastric ulcers, a duodenal ulcer, gastric angiodysplasia, esophageal varices, and an anastomotic ulcer.…”
Section: Selected Publications From Jpgn In 2022mentioning
confidence: 99%